2005
DOI: 10.1253/circj.69.1041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transmural Myocardial Perfusion by Ultra-Harmonic Myocardial Contrast Echocardiography in Reperfused Acute Myocardial Infarction

Abstract: pproximately 20-35% of angiographically successful recanalizations of the infarct-related artery in patients with acute myocardial infarction (AMI) fail to salvage ischemic myocardium because of a discrepancy between an open epicardial coronary artery and no blood flow in the damaged distal microvessels. [1][2][3][4] Regions with no-reflow show no improvement in regional function over time despite recanalization of the epicardial coronary vessels. These patients also have poorer global left ventricular (LV) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Both patient groups had little residual ongoing ischemic myocardial injury 1 h after reperfusion, as reflected by ST resolution. 6,26 However, the myocardium has been already irreversibly damaged in the former, whereas the latter patients had a relatively large amount of viable myocardium. It is plausible that more severe, rapidly progressing myocardial damage before and during reperfusion may no longer cause ST-segment elevation after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patient groups had little residual ongoing ischemic myocardial injury 1 h after reperfusion, as reflected by ST resolution. 6,26 However, the myocardium has been already irreversibly damaged in the former, whereas the latter patients had a relatively large amount of viable myocardium. It is plausible that more severe, rapidly progressing myocardial damage before and during reperfusion may no longer cause ST-segment elevation after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recent studies have shown that resolution of ST-segment elevation (ST resolution) on the 12-lead electrocardiogram (ECG) after reperfusion is associated with adequate microvascular perfusion in AMI and may predict smaller infarct size, better left ventricular (LV) function, and better outcomes. 7-10 However, we previously reported that some patients have a larger infarct size, LV dysfunction, and inadequate myocardial perfusion despite ST resolution, suggesting that ST resolution does not consistently predict myocardial salvage.…”
mentioning
confidence: 99%
“…After destroying microbubbles, the rate of replenishment of microbubbles into microvessels with low MI will reflect rate of blood transfer through the tissue. The underlying basis for assessing myocardial viability with MCE is that myocardial contrast enhancement depends on an intact microcirculation [11,12] . Shimoni et al [12] showed that in the segment with normal resting function, the microcirculation was preserved; in the dysfunctional segment that improved after revascularization, the microvascular density was normal; low capillary density and significant fibrosis were seen in the dysfunctional segments also that did not recover.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiograph-triggered end-systolic intermittent myocardial microvascular images with a mechanical index of 1.1-1.2 were acquired in the apical four-chamber view at incremental pulse intervals (triggering intervals of 1, 2, 4, and 6 cardiac cycles). 17 Three or four images were captured at each pulse interval. All cardiac images were analyzed using Volumap-445 software (YD Inc., Nara, Japan).…”
Section: Myocardial Contrast Echocardiography (Mce)mentioning
confidence: 99%